Pengaruh Motivasi dan Budaya Kerja Terhadap Komitmen dan Kinerja Penyuluh Pertanian di Kabupaten Jembrana (Jurnal Agribisnis dan Agrowisata, 2025)
The Impact of Motivation and Work Culture on the Performance of Agricultural Instructors in Jembrana Regency. The agricultural sector plays an important role in the implementation of development in Jembrana Regency. The role of agricultural extension agents is very much needed to contribute to agricultural development. Because the extension worker directly guides the farmers to produce the expected behavior change. The purpose of this study was to analyze the effect of work motivation and work culture on the performance of Agricultural Instructors in Jembrana Regency. This research was conducted from September to November 2020 at the Department of Agriculture and Food, Jembrana Regency. The location selection was made deliberately and the research sample consisted of 45 respondents (agricultural extension workers / direct supervisors) with the method of collecting data through questionnaires, then analyzed using quantitative methods using frequency distribution tables. The results showed that high motivation and a good work culture can increase the commitment of agricultural instructors in Jembrana Regency. Apart from that high commitment, good work culture and high motivation can also improve the performance of agricultural extension agents in Jembrana Regency. Efforts to maximize the performance of agricultural instructors in Jembrana Regency can be done by creating and optimizing the motivation, work culture and commitment of agricultural instructors properly.the implementation of development in Jembrana Regency.
Keywords: agricultural instructors; commitment; motivation; work culture